Use of Menstrual Cup in Turkish Women and Affecting Factors - Vasviye Eroğlu; Demet Çakır; Hilal Özbek (Nursing and Health Sciences Journal (NHSJ), 2024)
A menstrual cup is a menstrual hygiene product that collects the menstrual discharge into a container made from silicone or latex, which is elastic and reusable. Although menstrual cup use is becoming increasingly widespread in menstrual hygiene management due to environmental sensitivity and numerous positive features, it is still an unknown method in Türkiye. This study, therefore, set out to determine Turkish women's use of menstrual cups and the factors affecting it. The study sample, recruited through the snowball sampling method, consisted of 306 Turkish women aged between 18 and 49, and the data were collected using the Personal Information Form, Menstrual Hygiene Product Use Assessment Form, and Menstrual Cup Knowledge Level Assessment Form. The results indicated that the rate of menstrual cup use was 16.3%, and all the women using it were found to have sexual experience. It was discovered that cup users have higher satisfaction with their menstrual hygiene products since they are unnoticeable, cost-effective, environmentally friendly, non-infectious, non-restrictive to actions, and comfortable. Further, the presence of pain during menstruation and the variables of the menstrual hygiene product's noticeability through clothes, impact on environmental pollution, potential for causing infections, and restriction of actions are significant predictors of menstrual cup use. Significant differences were also detected between cup use and women's employment status, sexual experience, experiences during menstruation, pain during menstruation, social activity restrictions during menstruation, and recommending the product to others. To promote the widespread use of menstrual cups as a menstrual hygiene product, it is recommended that midwives, as primary advocates for women's reproductive health, conduct awareness and usage enhancement initiatives.